Numerical Simulation on the Induced Voltage Across the Coil Terminal by the Segmented Flow of Ferrofluid and Air-Layer - Lee, Won-Ho; Lee, Sangyoup; Lee, Jong-Chul (AMER SCIENTIFIC PUBLISHERS, 2018)
Nanoparticles and nanofluids have been implemented in energy harvesting devices, and energy harvesting based on magnetic nanofluid flow was recently achieved by using a layer-built magnet and microbubble injection to induce a voltage on the order of 10(-1) mV. However, this is not yet suitable for some commercial purpose. The air bubbles must be segmented in the base fluid, and the magnetic flux of the ferrofluids should change over time to increase the amount of electric voltage and current from energy harvesting. In this study, we proposed a novel technique to achieve segmented flow of the ferrofluids and the air layers. This segmented ferrofluid flow linear generator can increase the magnitude of the induced voltage from the energy harvesting system. In our experiments, a ferrofluid-filled capsule produced time-dependent changes in the magnetic flux through a multi-turn coil, and the induced voltage was generated on the order of about 101 mV at a low frequency of 2 Hz. A finite element analysis was used to describe the time-dependent change of the magnetic flux through the coil according to the motion of the segmented flow of the ferrofluid and the air-layer, and the induced voltage was generated to the order of 102 mV at a high frequency of 12.5 Hz.
Keywords: LINEAR GENERATOR; MAGNETIC FLUID